Evaluation of a magnetic method for the measurement of small intestinal transit time - Benmair, Y; Fischel, B; Frei, E H; Gilat, T (The American journal of gastroenterology, 1977)
A new method for the measurement of small intestinal transit time is described. An externally applied magnetic transducer senses the presence of an ingested ferromagnetic material--50 gm. of magnesium ferrite dispersed in a test meal--upon its arrival at the cecal area. The mouth-to-cecum transit time is thus determined. The method is noninvasive and is not associated with any radiation. The method was compared to the commonly used x-ray method and good correlation was found in 24 of 28 studies. The mean transit time in a group of 20 normal subjects was 157.5 +/- 63.9 min.